Morphological changes in the surface of enamel of primary teeth after application of ozone gas - Wagner, L.; Błaszczyk, A. (Polimery, 2015)
The aim of the study was to confirm if ozone gas provides morphological changes that promote increased adhesion forces of polymers to primary teeth enamel. The acquisition of enamel surface images using an AFM and an optical profiler made it possible to estimate the roughness indicators Rα, Rz and Rmax. It was assumed that the application of ozone gas provides morphological changes in the enamel of primary teeth based on increased surface roughness. It was also noticed that ozonated enamel is more prone to the action of H+ ions, which provides even more development of an adhesive surface.